CDK7 is a prognostic biomarker for non-small cell lung cancer - Kuempers, Christiane; Jagomast, Tobias; Heidel, Carsten; Paulsen, Finn-Ole; Bohnet, Sabine; Schierholz, Stefanie; Dreyer, Eva; Kirfel, Jutta; Perner, Sven (Frontiers in Oncology, 2022)
Aim: Non-small cell lung cancer (NSCLC) remains the leading cause of cancer-related death globally despite promising progress of personalized therapy approaches. Cyclin-dependent kinase 7 (CDK7) is a kinase involved in transcription, overexpressed in a broad spectrum of cancer types and found to be associated with an unfavourable prognosis. In this study, we aimed to investigate the protein expression of CDK7 in a large cohort of NSCLC incorporating adenocarcinomas (adNSCLC) and squamous cell carcinomas (sqNSCLC) and to correlate its expression with clinicopathological data. Methods: We performed immunohistochemical staining of CDK7 on our cohort of NSCLC including 258 adNSCLC and 101 sqNSCLC and measured protein expression via a semi-automated read out. According to the median value of CDK7 the cohort was stratified in a CDK7 high and low expressing group, respectively, and results were correlated with clinico-pathological data. Results: CDK7 was significantly higher expressed in sqNSCLC than in adNSCLC. In the group of sqNSCLC, CDK7 expression was significantly higher in sqNSCLC with lymph node metastases than in sqNSCLC with N0 stage. We found a significantly worse overall survival and disease-free survival for patients with CDK7 high expressing NSCLC. Conclusion: Since a high CDK7 expression seems to be linked with a poor prognosis it might serve as a promising novel prognostic biomarker and its assessment could be implied in future routine diagnostic workup of NSCLC samples. Considering that CDK7 inhibitors are currently tested in several trials for advanced solid malignancies, it may also be a new target for future anti-cancer therapy.